Retrospective immediate post-operative comparative study of sequential bilateral total knee replacement versus unilateral total knee replacement for knee primary osteoarthritis - Kamat, Sanil G.; Dessai, Rohan (International Journal of Research in Orthopaedics, 2021)
Background: The study is to compare the immediate post operative outcomes of sequential bilateral versus unilateral total knee replacement (TKR) for the treatment of primary knee osteoarthritis. Study comprised of 96 cases of tricompartmental knee primary osteoarthritis who have undergone unilateral and sequential bilateral total knee arthroplasty at Manipal Hospital, Goa from January 2016 to December 2018. The observations for each group was analysed and duration of hospital stay, post operative mobilisation, fall in haemoglobin level immediate post operative, need for blood transfusion, post operative complications, post operative pain and duration of surgery was recorded. The results were statistically compared. The mean duration of hospital stay, post operative blood loss in terms of fall in HB, post operative pain control, need of transfusions and duration of surgery revealed statistically significant differences. Methods: Total 96 patients diagnosed with primary tricompartmental osteoarthritis were divided into two groups retrospectively. Group 1 operated with sequential bilateral TKR under single anaesthetic procedure and group 2 with unilateral TKR both operated by same surgeon and anaesthetist. Results: It was observed that longer duration of surgery and hospital stay, higher fall in HB levels, increased need of analgesics and higher requirement of blood transfusions were associated with group 1 as compared to 2. Complication rates and post op mobilisation was similar in both groups. Conclusions: Sequential bilateral TKR is a viable option for patient with symptomatic bilateral knees but patient selection and pre op counselling takes the priority.